Rolling and Annealing Effects on Microstructure and Hardness of Commercial 405 Stainless Steel - A.K. Jahja; N. Effendi; M. Dani (Atom Indonesia, 2007)
The "cold-rolling" experiments for several values of true strain namely 5 percent, 10 percent, and 15 percent respectively have been carried out on commercial SS-405 steel samples at 350oC; the as-rolled samples were cut into several pieces in size of 10 x 10 x 5 mm3, and some pieces were annealed to 550oC for 24 hours. All samples were then mounted and polished before etching in order to observe the grain boundaries. The microstructure observation on all samples was carried out by using optical microscope (MO), meanwhile X-ray diffraction technique was employed in order to support the identification of the existing phases and to verify changes with respect to crystal orientation; the hardness tests were carried out by using Vickers micro hardness tester. The microstructure observation supported by X-ray diffraction results shows that the phase grains of rolled sample tends to take the oblong-shape, accompanied by a preferred orientation predominantly inclined toward the (110) plane. The microhardness testing results show that there has been an increase in the hardness of the as-rolled samples; Mainly because of the nearly negligible thickness of the original sample (being only 5 mm in size), the 15 percent as-rolled samples exhibits only a slight reduction in hardness compared to the 10 percent as-rolled samples; The main cause of this effect is the movement of some dislocations infiltrating the surface resulting in the reduction of the inner-stress in the bulk of the samples. In the rolled-annealed samples there is a very significant reduction in hardness compared to the as-rolled samples. Here the main cause is the recrystallization process taking place during annealing, which tends to significantly reduce the dislocations.